Castor (Ricinus communis L.) based cropping system for higher income in South-Western Haryana: Castor (Ricinus communis L.) based cropping system for higher income in South-Western Haryana - J S YADAV,; SATYJEET,; R S DADARWAL, (Journal of Oilseeds Research, 2020)
In Sirsa, Hisar and Rewari districts (Haryana) comparison of castor with traditional main cropping patterns viz.,cotton-wheat, cotton-mustard, pearl millet-wheat, pearl millet-mustard, cluster bean-wheat and cluster bean-mustard were compared with castor (sole) and castor with intercrops of cluster bean and mung bean. Sole castor recorded higher net returns (`46341/ha) than all the traditional cropping patterns though highest gross returns were in cotton- wheat cropping pattern (`95450 /ha). Highest net return (`54960/ha) and B:C (1.52) were recorded under castor based inter cropping systems.